The use of seating systems to reduce whole body vibration exposure in the SA industry - Gunaselvam, A. J. M. (Ariyamalar Jessica Miriam) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2004.